The biopsychosocial impact of hearing loss on people with hearing loss and their communication partners - Vas, Venessa Firmin (2017)
Hearing loss is a prevalent condition that can have negative implications on the day-to-day lives of those with hearing loss, and their communication partners. Several reviews have identified numerous questionnaires that explore the impact of hearing loss, with little consensus among researchers as to their preference. One reason for this is a lack of an agreed framework concerning exactly what is the impact of hearing loss, and what is important to those who live with the condition. To address this gap in understanding, the experiences of those living with hearing loss or with someone that has hearing loss was investigated using various systematic research methods and tools.